Estudo econômico da produção de tilápia do Nilo (Oreochromis niloticus) em tanques-rede - Fritzen, Nalva Alina (2015)
The objective of this study was to analyze the productive performance, the physical and chemical composition and the cost benefit of tilapia production (Oreochromis niloticus) in cages, in three different weight classes (500, 700 and 900g) termination. 24.000 fish were used, with initial weight of 150 ± 5,4 g for analysis of cost of production, over thirty cages of 6 m3 of useful volume. A sample of five fish for cage was harvested for yield performance, including 10% of those steaks were used for chemical analysis. To survey costs and profitability, we used the Operating Cost (Effective and Total), Depreciation, Total Cost and Profit. At the end it was observed that the smaller fish (500g) showed a smaller amount of lipids (1,76%) and visceral (3,69%) and a higher content of ash (1,40%) in the fillet. The best fillet yield and main trunk was found in larger fish (900g), 32,48% and 50,82% respectively. The profitability of production, the average fish (700g) stood out (19,77%).